2018
DOI: 10.1002/adma.201704825
|View full text |Cite
|
Sign up to set email alerts
|

Superfast Room‐Temperature Activation of SnO2 Thin Films via Atmospheric Plasma Oxidation and their Application in Planar Perovskite Photovoltaics

Abstract: The power conversion efficiency (PCE) of perovskite solar cells (PSCs) has now exceeded 20%; thus, research focus has shifted to establishing the foundations for commercialization. One of the pivotal themes is to curtail the overall fabrication time, to reduce unit cost, and mass-produce PSCs. Additionally, energy dissipation during the thermal annealing (TA) stage must be minimized by realizing a genuine low-temperature (LT) process. Here, tin oxide (SnO ) thin films (TFs) are formulated at extremely high spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 56 publications
2
52
0
Order By: Relevance
“…All XRD peaks for SnO 2 were indexable to the tetragonal SnO 2 structure, indicating the formation of pure SnO 2 crystals. In addition, the sputtered SnO 2 film on FTO glass showed high transmittance close to 90% in the visible region (Figure d), which is slightly higher than the high‐temperature‐processed spin‐coated SnO 2 film . These measurements convince that the room‐temperature‐sputtered SnO 2 has desirable properties as an effective ETL.…”
Section: Resultsmentioning
confidence: 64%
“…All XRD peaks for SnO 2 were indexable to the tetragonal SnO 2 structure, indicating the formation of pure SnO 2 crystals. In addition, the sputtered SnO 2 film on FTO glass showed high transmittance close to 90% in the visible region (Figure d), which is slightly higher than the high‐temperature‐processed spin‐coated SnO 2 film . These measurements convince that the room‐temperature‐sputtered SnO 2 has desirable properties as an effective ETL.…”
Section: Resultsmentioning
confidence: 64%
“…In addition, all the O 1s peaks are deconvolved into two individual peaks which originate from the fully coordinated lattice oxygen atoms (O L , 530.2 eV) and the hydroxide species (O H , 531.2 eV) . The hydroxide species is born of incomplete oxidation and high fluorine doping ratio . Hydroxide species would bring about shallow trap sites and thus decrease the mobility of SnO 2 and hinder the electron transport With increasing the treatment power, more hydroxide oxygen species turn into lattice oxygen which further confirms the formation of SnO 2 phase.…”
Section: Resultsmentioning
confidence: 92%
“…Currently, the most commonly used oxides include TiO 2 [2,15], ZnO [16] although a variety of other metal oxides [17,18], such as Nb 2 O 5 [19] and SnO 2 [20,21], may also be used, allowing some control of the interfacial properties and variability in junctions formed between electrodes and the CH 3 NH 3 PbI 3 layer. Recently, reports of new metal oxide-based PSCs have demonstrated that PCEs in the range of 15~20% are possible via development and optimization of new oxide layers [22][23][24][25][26][27][28][29][30]. These inorganic oxides are considered excellent interfacial materials due to their superior stability and electrical properties.…”
Section: Introductionmentioning
confidence: 99%